2015
DOI: 10.1166/jctn.2015.3785
|View full text |Cite
|
Sign up to set email alerts
|

Population and QTAIM Analysis of Metalloporphyrin–Fullerene Supramolecular Complexes

Abstract: We performed DFT calculations (with long-range corrected hybrid density functional wB97XD in 6-31G(d, 2p) Gaussian basis set) for the interaction of free porphine ligand and a number of its metal complexes with C 60 molecule. Its complexation mechanism was analized with the help of Hirshfeld, Mulliken and Bader's QTAIM analysis. We found that a selected DFT functional perfectly describes the intermolecular distances and leads to satisfactory formation energies. Population analysis indicated the presence of ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The energy of the porphyrin–fullerene non‐covalent interaction has been calculated by many authors for different porphyrins and by different methods . The results of the calculation depend strongly on the method used.…”
Section: Resultsmentioning
confidence: 99%
“…The energy of the porphyrin–fullerene non‐covalent interaction has been calculated by many authors for different porphyrins and by different methods . The results of the calculation depend strongly on the method used.…”
Section: Resultsmentioning
confidence: 99%
“…All quantum chemical calculations were performed with the Gaussian suite of programs at uωB97XD/6–311++G(2d,2p) level . Since formation of a H O hydrogen bond (HB) precedes formation of a HO covalent bond, we employed ωB97XD functional that is able to properly describe both weak and strong interactions . Presence of species with unpaired electrons required employment of unrestricted methods (uωB97XD).…”
Section: Methodsmentioning
confidence: 99%
“…Topological analysis of the electron density following the AIM theory was also used to investigate the noncovalent interaction mechanism of MP and fullerene (C 60 ) . According to the sign of the Laplacian of ρ ( ∇ 2 ρ ) calculated, it was found that all the interatomic interactions between fullerene and MP are closed shell interactions.…”
Section: Quantum Chemical Studies and Potential Applicationsmentioning
confidence: 99%
“…The BD is defined as the quotient between the total energy and the electronic density at the BCP; BD = H BCP / ρ BCP . The authors showed that the complexes containing FeP, MnP, and CoP would present transit closed shell interactions because BD < 0 . These interactions are considerably stronger than the pure closed shell ones that are van der Waals.…”
Section: Quantum Chemical Studies and Potential Applicationsmentioning
confidence: 99%